Factors Associated with Pap Smear Screening Test among Women Aged 15-49 based on Protection Motivation Theory - Fatemeh Jowzi; Tahereh Hashemifard; Mohammadali Morowatisharifabad; Zeinab Bashir (حیات, 2013)
Background & Aim: Cervical cancer is the fourth common cancer worldwide. Pap smear is a usual t est to screen cervical cancer. The aim of the present study was to determine factors associated with Pap smear screening among married women aged 15-49 years in Lamerd health centers based on the Protection Motivation Theory .   Methods & Materials: In this cross-sectional study, 220 married women aged 15-49 years were selected. Data were gathered using a questionnaire designed based on the Protection Motivation Theory. The questionnaires were completed via individual interviews with the participants. Validity and reliability of the questionnaire were approved. Data were analysed using the Kruskal-Wallis, U-Man Whitney test and c 2 in the SPSS-16.   Results: Most of the participants ( 40%) had a high school diploma and 70% of them were housewives. Most of the participants (65.6%) had used the test once at least. There were statistically significant relationships between the use of Pap smear with the protection motivation against cervical cancer (P<0.001 ), perceived self-efficacy ( P =0.002 ), perceived response efficacy ( P =0.007 ) and perceived costs ( P <0.001 ) .   Conclusion: Regarding the statistically significant relationships between the constructs of the Protection Motivation Theory and the use of Pap smear screening test among women , it is recommended to design educational programs based on the Protection Motivation Theory to encourage married women for using Pap smear screening test.